Application of the Team-Assisted Individualization Learning Model to Improve Students' Critical Thinking Skills in Mathematics in Fourth Grade Elementary Schools - Ade Mustika Andari; Melly Andriani; Mhmd Habibi; Risna Wati Risna Wati (Universitas Riau, 2023)
This study describes the improvement of the Team Assisted Individualization learning model in the fourth grade of SD Negeri 028 Kubang Jaya in improving students' mathematical critical thinking skills. This research is classroom action research, which consists of two cycles. The subjects in this study were one teacher and fifteen fourth-grade students at 028 Kubang Jaya Elementary School. Data collection was carried out through observation, testing, and documentation, with qualitative data analysis using percentages. Based on the research results and data analysis, it was shown that before the action, 11 (73%) students were in the less critical category, and 3 (20%) students were in the critical category. 6.6% of students are in the quite critical category. Team-assisted, individualized learning applies remedial actions. After taking corrective action with the team-assisted individualization learning model. Then corrective action is taken with the team-assisted individualization learning model. In cycle I, students' critical thinking skills increased; 6 students, or 40%, were in the critical category, and 9 students, or 60%, were in the moderately critical category. Furthermore, in cycle II, the ability to think critically has increased: 8 students, or 53%, are in the very critical category, 4 students, or 26%, are in the moderately critical category, and 3 students, or 20%, are in the critical category. In cycle II, students' critical thinking skills have achieved the target success of the action set. Thus, it can be concluded that the application of the team-assisted individualization learning model can improve students' critical thinking skills in fourth-grade mathematics at Public Elementary School 028 Kubang Jaya.